A Trojan Feast: The Food and Drink Offerings of Aliens, Faeries, and Sasquatch by Joshua Cutchin - Alexander, John B (Journal of Scientific Exploration, 2015)
The bottom line is that if you find yourself abducted, invited, or otherwise in the company of sentient nonhuman entities, don’t ingest any of their items of sustenance that they might offer. Cutchin reveals many tales of people who have reported such encounters and provides details about the different characteristics of the provisions. Chapters delineate breads, liquids, fruits, pills, and on rare occasions meats that are offered for a variety of reasons that range from drugging the victim, preventing them from leaving the altered realm and returning to their real world, to providing cures for current illnesses. Prohibitions aside, those presented with things to eat or drink often are not provided the option of whether or not to partake. All of the book’s research is based on an extensive literature search. Heavily annotated, the book with 186 pages containing script has 417 specific references and an additional 24 pages of bibliography. From a critical perspective it is the farrago of source material that is problematic. The veracity of citations varies widely. There are established credible sources such as Jacques Vallee, Thomas Bullard, Dennis McKenna, and others with known qualities of research. Then there are sources listed with unknown authors and taken from newsletters, tabloids, and the Internet with highly questionable provenance. Global in nature, the reports fluctuate from firsthand accounts of encounters with strange beings to reiteration of popular folklore.